Pengembangan Media Pembelajaran E-Book Berbasis Android untuk Meningkatkan Literasi Finansial Siswa SMK - Masruchan Masruchan; Rifa Nurmilah (Lembaga Pengembangan Kinerja Dosen, 2025)
The rapid development of digital technology and the increasing complexity of financial products, from digital wallets and bank loans to cryptocurrency and investment platforms, highlight the urgent need for financial literacy education, particularly for vocational high school (SMK) students in Indonesia. Many SMK graduates directly enter the workforce or pursue entrepreneurship without attending university, making financial decision-making skills crucial. This article explores the potential of Android-based e-books as an innovative and accessible learning medium to enhance students’ financial literacy. Designed to be interactive, contextual, and engaging for Gen Z learners, the proposed e-book serves as a pedagogical supplement, not a replacement, to classroom teaching. Drawing from literature reviews, examples of existing apps, and relevant educational frameworks, the article emphasizes the importance of developing localized, curriculum-aligned digital resources. The paper concludes with suggestions for evaluating financial learning apps and recommends steps for integrating them effectively into SMK education.